For the PMOS given below I can derive the function f, such that f inverted in its variables corresponds to the expression of PMOS(f) and f inverted equals NMOS(f).

For this specific problem I have however two contradicting solutions and thus would be happy, to have a 2nd opinion.

My solution:

\$ f(a,b,c) = (\bar{a} + \bar{b})(\bar{a}\bar{b} + \bar{c}) \$

\$ PMOS(f(a,b,c)) = (a + b)(a b + c) \$

\$ NMOS(f(a,b,c)) = a b + c(a + b) \$

Suggested solution:

\$ f(a,b,c) = \dots \$, not available

\$ PMOS(f(a,b,c)) = (\bar{a} + \bar{b})(\bar{a}\bar{b} + \bar{c}) \$

\$ NMOS(f(a,b,c)) = \overline{a b + c(a + b)} \$

The differences between the expresseions are not much, nonetheless I would like to know, what is correct, what is wrong.

In the image below, Erdung can be translated to ground or earthing.



PMOS is equivalent to fitting a Not Gate on every input.

I reached this by making the truth table and simplifying, the main differences in your equations look to be from missing the simplification with B*C. when they are both true, you do not care about A.


enter image description here

PMOS = A'*B'+B'*C'

enter image description here

|improve this answer|||||
  • \$\begingroup\$ Doubt that: You have \$ \bar{f} = NMOS(f) \Rightarrow f = \overline{AB + BC} = \bar{A} \bar{B} + \bar{B} \bar{C}+ \bar{A} \bar{C} \$ \$ \Rightarrow PMOS(f) = AB+BC+ AC \neq \bar{A} \bar{B} + \bar{B} \bar{C} \$ \$\endgroup\$ – Imago Sep 9 '19 at 16:28

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.